Crime pattern activities based on weather changes towards the quality of life / Anis Zulaikha Mohd Zukri, Siti Rasidah Md Sakip and Suraya Masrom - Mohd Zukri, Anis Zulaikha; Md Sakip, Siti Rasidah; Masrom, Suraya (2022)
Sustainable Development Goals (SDGs) are often associated with significantly improving the quality of life, encompassing economic, social, and physical well-being and development systems that ensure satisfaction. Furthermore, safety and security are closely linked to and introduced into the SDG planning policy to improve the community's quality of life. The gap in the paper is the weather is widely known to impact the environment. Still, it is uncommon to notice how weather change affects crime activity patterns and quality of life. A few kinds of literature investigating empirical studies have also focused on social consequences, particularly migration and social conflict. However, criminal cases are also one of the factors to the quality of life. Studies linking crime and the environment are tremendously established. Thus, this paper identifies the pattern of criminal activity based on weather changes to address this situation. In addition, according to several previous research studies from various regions around the world, research on weather and crime was found to have a significant correlation. Thus, weather can be used as an instrumental variable to study the impact of crime on various variables, including indices of quality of life, property value and economic growth. In this paper, the research methodology uses quantitative data. The data were gathered from the Royal Malaysian Police (RMP) and the Meteorological Department for Selangor, Kuala Lumpur and Johor from 2011 to 2020. RMP provide a property dataset divided into six categories: theft, vehicle theft, motorcycle theft, van/lorry/truck theft, snatch and burglary. The Meteorological Department provides a temperature and humidity dataset for the weather data. The data were analyzed using SPSS statistical and illustrated in the bar graph method to identify the pattern and relationship between weather and crime. Further research needs to be done to better enhance research results by studying current data and patterns of weather and crime to correlate the relationship between crime and weather towards the quality of life.